Students' Vocabulary Learning Strategies in the English Education Program at STKIP Al Amin Dompu: A Qualitative Study - Putu Dewi Novita Sari Putu Dewi Novita Sari; Masita Masita; Putri Ayuningtyas Putri Ayuningtyas (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2026)
Vocabulary knowledge is a cornerstone of English language proficiency, yet many EFL students struggle with vocabulary acquisition. This qualitative study explores the vocabulary learning strategies (VLS) employed by students in the English Education Program at STKIP Al Amin Dompu. Using a phenomenological approach, data were collected through semi-structured interviews with twelve second-semester students. Thematic analysis revealed that students employ a range of strategies across Schmitt's (1997) taxonomy, including determination strategies (bilingual dictionary use, contextual guessing), social strategies (consulting teachers and peers), memory strategies (repetition, note-taking), cognitive strategies (media engagement), and metacognitive strategies (self-monitoring). However, students predominantly relied on surface-level strategies such as bilingual dictionary use and verbal repetition, while deeper processing strategies like systematic goal-setting and contextual analysis were underutilized. Key challenges included limited awareness of diverse strategies, difficulties in vocabulary retention, and the gap between declarative knowledge of strategies and their consistent application. The findings suggest pedagogical implications for explicit VLS training to foster autonomous, self-regulated vocabulary learning among EFL students in Indonesian higher education.